Pengembangan Media Pembelajaran Ekonomi Berbasis Android Dengan Platform Kodular Pada Materi Pengantar Ilmu Ekonomi Untuk Siswa Kelas X di SMAN Balung Kabupaten Jember Tahun Ajaran 2022/2023 - Nimas Satriani; Hety Mustika Ani; Lisana Oktavisanti Mardiyana (Universitas Negeri Surabaya, 2023)
This research was carried out with the aim of developing an android- based economic learning media with the KODULAR platform in an interesting and effective Introduction to Economics material for class X students at SMAN Balung, Jember Regency. This type of research is development research with the ADDIE model which is limited to the implementation stage. This study used four research instruments, namely validation sheets, questionnaires, interviews, and documents. Data analysis techniques applied include testing the level of attractiveness and level of effectiveness. The results of this study indicate that the developed economic learning media is attractive with a limited group trial percentage of 89.85% and a large group trial percentage of 93.78% with very attractive criteria. The developed media is also effective because it can achieve learning objectives, showing an increase in student scores in the limited group trial from 80.80 to 89.20 and in the broad group trial from 80.22 to 90.11. Thus, these learning media are categorized as interesting and effective learning media.